UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MEDIA KONKRET TERHADAP PESERTA DIDIK KELAS III DI SDN 61 PALEMBANG - Melyana; Hetilaniar; Mega Kusuma Putri (STKIP Subang, 2026)
This study aims to improve the mathematics learning outcomes of third-grade students through the use of concrete media at SDN 61 Palembang. The background of this research is based on the low mathematics learning outcomes of students, particularly in their ability to understand fundamental mathematical concepts which are still considered abstract for elementary school students. The use of less varied instructional methods has resulted in students being less active, less motivated, and experiencing difficulties in understanding the learning materials. Therefore, concrete media are employed as an alternative instructional approach to assist students in comprehending mathematical concepts in a more tangible, meaningful, and easily understandable manner. This study employed the Classroom Action Research (CAR) method which was conducted in two cycles. Each cycle consisted of four stages: planning, action implementation, observation, and reflection. The subjects of the study were 34 third-grade students. Data were collected through observation, learning outcome tests, and documentation. The data analysis was carried out using both quantitative and qualitative descriptive approaches by comparing the improvement in students’ learning outcomes in each cycle. The results of the study indicated that the use of concrete media was effective in improving students’ mathematics learning outcomes. In the pre-cycle stage, the average student learning outcomes were still below the Minimum Mastery Criteria (MMC). The percentage of learning mastery reached only 46%, with an average score of 46.50. After the implementation of concrete media in Cycle I, the level of learning mastery increased to 61%, with an average score of 63.94. Although students’ learning outcomes showed improvement, several students had not yet achieved the expected level of mastery. In Cycle II, the improvement in learning outcomes became more significant, increasing to 91% with an average score of 89.34, indicating that the majority of students had successfully achieved the MMC. In addition to improving learning outcomes, the use of concrete media was also able to enhance students’ activeness, motivation, and interest in participating in the mathematics learning process. Therefore, concrete media have proven to be effective in helping students understand mathematical concepts more easily and in a more enjoyable manner.